Mentoring Faculty as Department Chair - Lynn Shollen (Academic Chairpersons Conference Proceedings, 2020)
Mentoring is a powerful strategy for facilitating faculty and department success. Participants will engage in multiple case study analyses in teams, individual reflection followed by group processing, and interactive discussions and activities to dig into challenges that faculty encounter at different career stages and strategies Chairs can leverage to mentor those faculty, as well as disengaged or disgruntled faculty.
Keywords: Mentoring; faculty development; faculty relationships; career success